The earthquake-resistance of flush end-plate joints - Thomson, Andrew William (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2002)
This thesis investigates the applicability of flush end-plate joints to frames in low-to-moderate seismic zones. Although a great deal of research has been carried out on the use of semi-rigid joints in frames, most of this has concentrated on the monotonic, rather than the cyclic or dynamic response of the joints. In addition, the majority of research has examined angle and extended endplates. Flush end-plate joints are advocated for use in the wind-mom ent design method in the United Kingdom and considerable design guidance is available.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin